Phase transitions of cesium azide at pressures up to 30 GPa studied using in situ Raman spectroscopy - Medvedev, S. A.; Barkalov, O. I.; Naumov, Pavel; Palasyuk, Taras; Evers, J.; Klapoetke, T. M.; Felser, Claudia (Journal of Applied Physics, 2015)
Cesium azide has been studied by Raman spectroscopy at pressures up to ?30 GPa at room temperature. The sequence of phase transitions to Phase III (at 0.5 GPa), Phase IV (at 4.3 GPa), and Phase V (at ?19 GPa) has been observed in agreement with recent X-ray diffraction studies. Phase III has been found to adopt a monoclinic C2/m structure with two azide anions in nonequivalent positions, where one set of azide anions appears to be orientationally disordered according to the observed Raman spectra. The transition to Phase IV has been associated with orientational ordering of azide anions, while the transition to Phase V has been shown to proceed with a lowering of crystal symmetry. Moreover, spectroscopic features indicate a possible change of bonding in CsN3 toward formation of covalent bonds at high pressures.
CRIS-Team Scopus Importer:2023-03-20